FEASIBILITY INDICATORS OF STUDY BOOKS USED ELEMENTARY SCHOOL STUDENTS - Bayu Purbha Sakti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Suicide primary school girls, 2 reporting discourses, and zoning system require that each elementary school has books that attract students and teachers to read them. Negative content and typing errors written in the book will cause different understandings experienced by elementary school students. Elementary school student who have good linguistic intelligence will be easy to memorize and have extensive vocabulary. Elementary school student with high visual-spatial intelligence will be active in the imagination. Books used by primary schools must meet the values and norms applicable in the community. Primary schools are required to evaluate all the books used in primary schools. Sanctions are granted to authors and publishers if any incorrect information is written in the book. Primary school students will think positively or negatively by looking at textbooks. Eligibility of elementary school textbooks is the responsibility of many parties in the field of education even though teachers are an important component that should assess the appropriateness of textbooks.